Procession of The Traditional Custom of “Bubus Dise” in BatuJai Village to Support Sustainable Tourism Village - Saleh, Nur Hud; Lestari, Erin Yudia; Murianto; Faizin, Muhammad (International Journal of Green Tourism Research and Applications, 2025)
This study explores the Bubus Dise traditional ceremony in Batujai Village, Central Lombok, and analyzes its potential as both a cultural heritage asset and a sustainable tourist attraction. The Bubus Dise ceremony is a sacred ritual the local community performs to purify the village from misfortune, disease, and negative spiritual influences. Beyond its ritualistic function, the ceremony strengthens the community’s social bonds and spiritual values. The research employed a qualitative descriptive methodology, incorporating observation, in-depth interviews with community leaders and cultural practitioners, and a review of relevant literature. The findings reveal that the Bubus Dise tradition holds substantial potential as a cultural tourism offering. It not only preserves the unique cultural identity of the village but also contributes to the local economy through tourism-related opportunities. Moreover, the tradition aligns with the principles of sustainable tourism, particularly through its emphasis on cleanliness, greening efforts, and the integration of the “Seven Charms” tourism development programs. Despite these opportunities, the ceremony faces challenges due to modernization and the growing influence of commercial tourism, which may risk diluting its authenticity. The study concludes by offering recommendations to support the sustainable development of Bubus Dise as a cultural tourism attraction. These include community-based tourism planning, heritage preservation initiatives, and policy support to maintain cultural integrity while promoting responsible tourism.